Relapse prevention therapy: an integrated approach to the treatment of alcohol disorders and comorbid anxiety : a review of literature on anxiety, alcoholism and relapse prevention therapy - recommendations for clinical psychology groups conducted as part of an inpatient alcohol rehabilitation programme in the Western Cape - Rufus, Brett Charles (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--University of Stellenbosch, 2004.